The Role of Emir Abdelkader in Establishing The Principles Of International Humanitarian Law (مجلة الواحات للبحوث والدراسات, 2026)
War has become one of the most prominent features of human history, wars and conflicts in ancient times were characterised by brutality and excessive bloodshed, over time, there was an urgent need to establish rules that should be adhered to during such conflicts, leading to the conviction that combat should be subject to humanitarian principles. Among the things mentioned about Emir Abdelkader of Algeria is that during his battles against the French colonial invasion of Algeria, he established and applied a set of laws relating to the treatment of prisoners and detainees from the enemy army, among these laws was the consideration of any Frenchman captured in battle as a prisoner of war, to be treated as such until an opportunity arose to exchange him for an Algerian prisoner, he also categorically prohibited the killing of unarmed prisoners and stipulated that any arab holding a French prisoner must treat him well.